USING MNEMONIC TECHNIQUES IN VOCABULARY LEARNING - Ita Purnama (International Conference on Education and Language (ICEL), 2016)
This paper aims to find out how to apply the mnemonic techniques in vocabulary learning. Many methods, strategies, approaches and techniques are created to improve vocabulary master in learning process. Mnemonic is one of technique to train good vocabulary because mnemonic techniques are focus on memorizing things and it’s really suitable for vocabulary learning. Mnemonic techniques consist of: a) acronyms, b) sentences/acrostics, c) peg method, d) image mnemonic, f) chunking, and g) mind maps. Mnemonic techniques enable the student to explain about their experience, environment, place, things, etc. and systematically store new vocabulary in his or her brain which can be accessed easily without need more time to do it.